A new species of Cyrtodactylus (Squamata: Gekkonidae) from the limestone forest of Khammouane Province, central Laos - Luu, Vinh Quang; Calame, Thomas; Nguyen, Truong Quang; Bonkowski, Michael; Ziegler, Thomas (Zootaxa, 2015)
We describe a new species of the genus Cyrtodactylus on the basis of three specimens from Khammouane Province, Laos. Cyrtodactylus soudthichaki sp. nov. is distinguished from the remaining congeners by the combination of the following characters: adult SVL 69.2–70.0 mm; dorsal head and neck with dark blotches; nuchal loop present; dorsum with five brown bands between limb insertions; 19 or 20 irregular rows of dorsal tubercles; 32 or 33 ventral scale rows; ventrolateral folds present, with distinct tubercles; dorsal surface of hind limbs with tubercles; 29 precloacal and femoral pores in a continuous row in males, precloacal pores absent in the female; enlarged femoral and precloacal scales present; 4 or 5 postcloacal tubercles; and subcaudals transversely enlarged. The new species most closely resembles Cyrtodactylus jaegeri and Cyrtodactylus roesleri in overall coloration and pattern. However, they can be clearly distinguished from each other in the number of dorsal tubercle rows, ventral scales, and femoral and precloacal pores. Cyrtodactylus soudthichaki is the 16th species of Cyrtodactylus known from Laos.